Etiology of Oral Potentially Malignant Disorders and Squamous Cell Carcinoma Based on Cellular Stress Regulation and Matrix Stiffness - Toshihiro Hasegawa; Takehito Ouchi; Yoshiyuki Shibukawa; Seiji Asoda; Taneaki Nakagawa (Frontiers in Bioscience-Landmark, 2023)
The oral cavity serves as the initial segment of the digestive system and is responsible for both nutritional supplementation and the mechanical breakdown of food. It comprises distinct hard and soft tissues; the oral mucosa is subject to mechanical stress and interaction with microbiota. In oral cancer, tumors exhibit abnormal cellular networks and aberrant cell-cell interactions arising from complex interplays between environmental and genetic factors. This presents a challenge for clinicians and researchers, impeding the understanding of mechanisms driving oral cancer development and treatment strategies. Lesions with dysplastic features are categorized under oral potentially malignant disorders, including oral leukoplakia, erythroplakia, oral submucous fibrosis, and proliferative verrucous leukoplakia, carrying a high malignancy risk. In this review, we discuss oral cancer cell characteristics and the stiffness of the surrounding matrix. We also discuss the significance of stiffness equilibrium in oral potentially malignant disorders, particularly oral submucous fibrosis, possibly triggered by mechanical stress such as betel quid chewing.